Information panels and scenic illumination as important elements of ruin presentation - Jakub Novotný; Dita Machova (Ochrona Dziedzictwa Kulturowego)
This paper is focused on the issue of information panels and the illumination of monuments, especially ruins. First, methodological recommendations of ICOMOS Charter for the Interpretation and Presentation of Cultural Heritage Sites are mentioned as it is necessary to follow the recommendations when planning and implementing any interpretive infrastructure. There follows a brief characteristic of the function, intervention, positive and negative of the information panels as important elements of the interpretative infrastructure. Similarly, scenic illumination of monuments is presented. Two case studies of installation of information panels are than described - Jihlava Town Fortification (CZ) and Remains of Slav Hill Fort. The conclusion than offers methodological steps for the choice of solution and realisation of interpretive infrastructure.